2018
DOI: 10.1039/c7fo01720k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a galacto-oligosaccharide-rich diet on fecal microbiota and metabolite profiles in mice

Abstract: Galacto-oligosaccharides (GOS) are prebiotics that positively affect the host's gut microbiota, which is important for the health of the host. Most previous studies focused on specific flora components (e.g. Bifidobacterium and Lactobacillus); very few have investigated the relationship between flora and metabolites. Here, we used 16S rRNA analysis and metabolomics to analyze the effect of GOS on microbiota and metabolites. Results show that the abundance of Ruminococcaceae and Oscillibacter decreased signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 37 publications
5
40
0
Order By: Relevance
“…Using a diet-induced hamster model of hypercholesterolemia, Lin and colleagues demonstrated that DSW also led to signi cant reductions in triglycerides, LDL, and total cholesterol, although Bacteroidetes was the only bacterial population signi cantly correlated with serum cholesterol and LDL in response to the high cholesterol diet [19]. Increases in Parasutterella in response to GOS supplementation in mice were associated with signi cant reductions in triglycerides but not LDL levels [22]. Parasutterella levels were inversely correlated with fat consumption but not total energy intake in obese people [23].…”
Section: Discussionmentioning
confidence: 99%
“…Using a diet-induced hamster model of hypercholesterolemia, Lin and colleagues demonstrated that DSW also led to signi cant reductions in triglycerides, LDL, and total cholesterol, although Bacteroidetes was the only bacterial population signi cantly correlated with serum cholesterol and LDL in response to the high cholesterol diet [19]. Increases in Parasutterella in response to GOS supplementation in mice were associated with signi cant reductions in triglycerides but not LDL levels [22]. Parasutterella levels were inversely correlated with fat consumption but not total energy intake in obese people [23].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that this mixture of GOS is able to increase the blood level of interleukin 8 (IL-8) and C-reactive protein and to improve Natural Killer (NK) cell activity [51]. Finally, an in vivo study showed that supplementation with GOS in mice also improved lipid metabolism, without a positive effect on glycemic metabolism and with a significant enrichment of Alloprevotella, Bacteroides, and Parasutterella in the mouse microbiota [52].…”
Section: Gosmentioning
confidence: 99%
“…Can modulate immune function: ↑ Cytokine IL-10, interleukin 8 (IL-8) and C-reactive protein, improve Natural Killer (NK) cell activity, and ↓ IL-1β expression [51]. Improve lipid metabolism [52]. Enrich the mouse microbiota of Alloprevotella, Bacteroides, and Parasutterella [52].…”
Section: Galactooligosaccharides (Gos)mentioning
confidence: 99%
See 1 more Smart Citation
“…Many pieces of literature have verified that gut microbiota alterations affected host metabolism, including nutrient digestion, lipid metabolism, and energy metabolism [7,8], indicating that gut microbiota could be considered as a potential target for the prevention or treatment of obesity and related chronic diseases. In the phylum level, gut microbiota is mainly composed of Firmicutes, Bacteroidetes, Verrucomicrobia, Saccharibacteria, Actinobacteria, and Proteobacteria [9]. Studies have shown that compared with healthy individuals, the proportion of Bacteroides decreased and the proportion of Firmicutes increased in obese people.…”
Section: Introductionmentioning
confidence: 99%